Diabetes-associated central nervous system mucormycosis with delayed diagnosis: a case report - Jia, Geng; Yang, Changchun; Feng, Yi (Frontiers in Neurology, 2025)
BackgroundCentral nervous system (CNS) mucormycosis is a rare, life-threatening fungal infection predominantly affecting diabetic and immunocompromised patients. Early diagnosis remains challenging, resulting in poor outcomes. We report a case highlighting the diagnostic challenges and rapid progression in a patient with uncontrolled diabetes and COVID-19 infection.Case presentationA 31-year-old male with untreated type 2 diabetes mellitus presented with severe pneumonia due to COVID-19 infection. His condition rapidly deteriorated, developing CNS symptoms and characteristic nasal lesions. Cerebrospinal fluid (CSF) analysis revealed lymphocytic pleocytosis, high protein, and low glucose. Metagenomic next-generation sequencing (mNGS) of CSF confirmed Rhizopus oryzae infection. Despite initiating amphotericin B therapy, his condition worsened.ResultsThe patient succumbed to progressive multi-organ failure secondary to disseminated mucormycosis. This case emphasizes the significance of uncontrolled diabetes and COVID-19 as critical risk factors and highlights the diagnostic utility of CSF mNGS.ConclusionPrompt recognition of risk factors, early utilization of advanced diagnostic methods, and aggressive treatment are essential to improve outcomes in CNS mucormycosis.